2003
DOI: 10.1167/iovs.03-0342
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Adult Bone Marrow-Derived Stem Cells in Choroidal Neovascularization

Abstract: Adult stem cells are recruited to the choroid in a model of CNV, where they contribute to forming aberrant new vessels. This observation suggests that targeting stem cell recruitment to the eye may offer a novel therapeutic strategy for ARMD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(102 citation statements)
references
References 20 publications
3
98
1
Order By: Relevance
“…[82][83][84]136 The abnormal local response may also compromise the systemic input from the bone marrow or both local and systemic components could be blunted by co-existent disease. 34,71,121,137 In summary, it appears that the process that is DyR generates the stereotypical and even predictable wound response that is seen in AMD. As outlined in the previous sections of this study, all the necessary molecular ingredients appear to be present, to generate a normal reparative response.…”
Section: Bringing It All Together: Amd and Dyrmentioning
confidence: 93%
See 1 more Smart Citation
“…[82][83][84]136 The abnormal local response may also compromise the systemic input from the bone marrow or both local and systemic components could be blunted by co-existent disease. 34,71,121,137 In summary, it appears that the process that is DyR generates the stereotypical and even predictable wound response that is seen in AMD. As outlined in the previous sections of this study, all the necessary molecular ingredients appear to be present, to generate a normal reparative response.…”
Section: Bringing It All Together: Amd and Dyrmentioning
confidence: 93%
“…[58][59][60][61][62] Of course the expression of SDF-1 and VEGF also highlights the role of vasculogenesis in SRNV, although again the precise mechanism of how this is achieved is unclear. 34,63,71 The role of VEGF in NV is also intimately associated with the angiopoietins and their tyrosine kinase receptors Tie-1 and Tie-2 that are expressed on endothelial cells and also on some macrophage subtypes involved in angiogenesis. 72 Initially, Ang-2 expression, in concert with VEGF, promotes vascular instability and promotion of endothelial cell sprouting.…”
Section: Subretinal Neovascularisationmentioning
confidence: 99%
“…It is now more and more accepted that new blood-vessel formation in post-natal events not only relies on angiogenesis, but also on vasculogenesis, the recruitment and differentiation of BM-derived angioblasts into mature endothelial cells. EPCs and hematopoietic progenitor cells (HPCs) are both recruited from BM and contribute to CNV [23,24]. When injected systemically into adult mice, BM-derived cells incorporated into experimentally induced CNV [24].…”
Section: Inflammation Angiogenesis and Vasculogenesis In Cnvmentioning
confidence: 99%
“…EPCs and hematopoietic progenitor cells (HPCs) are both recruited from BM and contribute to CNV [23,24]. When injected systemically into adult mice, BM-derived cells incorporated into experimentally induced CNV [24]. Engraftment of irradiated C57Bl/6 mice with BM issued from green fluorescent protein (GFP)-transgenic mice led to detection of GFP-positive cells (macrophages, endothelial cells and vascular smooth-muscle cells) in CNV [23].…”
Section: Inflammation Angiogenesis and Vasculogenesis In Cnvmentioning
confidence: 99%
“…It was reported that about 45% cells in laser-induced CNV was bone marrow derived. Meanwhile, BMCs also modulate the severity of CNV [16][17][18]. During this process, it is well-known that stromal cellderived factor-1 (SDF-1) is involved in recruiting BMCs and also promoting CNV development [19].…”
mentioning
confidence: 99%